Children’s Participation: Questioning Competence and Competencies? - Le Borgne, Carine (Social Inclusion, 2017)
While Article 12 of the Convention on the Rights of the Child has encouraged children’s participation in collective decision-making, the literature is replete with the challenges as well as successes of such participation. One challenge is adults’ perceptions of children’s competence and competencies. These are frequently used as threshold criteria, so that children viewed as incompetent or lacking competencies are not allowed or supported to participate. Despite this casual elision between children’s participation and their (perceived) competence and competencies, the latter are rarely explicitly defined, theorised or evidenced. This article draws on research undertaken in Tamil Nadu (South India) and Scotland (UK), with two non-governmental organisations supporting children’s participation in their communities. The article examines how staff members can validate and enhance children’s competence and competencies, by scaffolding children to influence decision-making and recognising and adding to children’s knowledge. These empirical findings suggest the need for increased scrutiny of the concepts of competence and competencies, recognising their disempowering potential. The findings argue that competence is situationally and socially constructed rather than a set and individual characteristic.